Association of recent exposure to ambient metals on fractional exhaled nitric oxide in 9-11 year old inner-city children - Rosa, Maria José (2014)
Exposure to ambient metals in urban environments has been associated with wheeze, and emergency room visits and hospitalizations due to respiratory illness. However, the effect of ambient metals exposure on airway inflammation, and how these associations may be modified by seroatopy, has not been determined. Fractional exhaled nitric oxide (FENO) is a reliable proxy marker of airway inflammation. We hypothesized that recent ambient concentrations of Ni, V, Zn and Fe would be associated differentially with proximal and distal fractions of exhaled NO, and that these associations would be modified by seroatopy. As part of the Columbia Center for Children’s Environmental Health (CCCEH) birth cohort study, 9-11 year old children (n=192) were evaluated. Ambient measures of Ni, V, Zn and Fe were obtained from a local central monitoring site and averaged over nine days based on three 24 hour measures every third day. Fractional exhaled nitric oxide (FENO) samples were obtained at constant flows of 50 (FENO(50)), 83 and 100 mL/sec, and used to determine surrogate measures for proximal (JNO) and alveolar (Calv) inflammation. Seroatopy was determined by specific IgE at age 7. Data were analyzed using multivariable linear regression. Ambient V and Fe concentrations were associated positively with FENO(50) (p = 0.018, p = 0.027). Ambient Fe was associated positively with JNO (p = 0.017). Ambient Ni and V concentrations were associated positively with Calv (p = 0.004, p = 0.018 respectively). A stronger association of Ni concentrations with Calv was observed among the children with seroatopy. These results suggest that ambient metals are associated differentially with different fractions of FENO production, and this relationship may be modified by seroatopy.